Transitioning to high efficiency air conditioning in Saudi Arabia: A benefit cost analysis for residential buildings. (September 2020) - Krarti, M.; Howarth, Nicholas
Abstract: This paper assesses the benefits of transitioning to high efficiency air conditioning (AC) equipment for existing units specific to the residential building stock in the Kingdom of Saudi Arabia (KSA). The analysis is based on a calibrated residential building stock model for Saudi Arabia supported by national statistics regarding the characteristics of AC systems. Various housing prototypes, vintages, and locations are included in the analysis. Specifically, the analysis considers the scaling up of the government's High Efficiency AC (HEAC) program which offers 900 Saudi Riyals (240 USD) per unit to consumers for up to 6 split system units with an energy efficiency rating (EER) of 13.0 or more per household. The main findings of the study suggest that upgrading the existing old stock of window units and split systems currently in place to the requirements of HEAC program would generate a reduction in electricity consumption of around 33 TWh/year and 24 million tons of CO2 . Due to the effect of the HEAC consumer subsidy, purchasing a high efficiency unit has a simple payback period for the consumer of 5 years which is faster than less efficient AC options. This would come at a cost to the government of approximately 6 Billion USD resulting in an annual income of 3.0 Billion USD from the sale of avoided fuel associated with the saved electricity consumption. Highlights: Improving energy efficiency of Saudi residential AC stock can save 33 TWh per year. Phasing out window AC systems can result in electricity savings of 20 TWh per year. Stringent MEPS for ACs can lower carbon emissions by 24.0 Million-Tons annually. Saudi government can recover in 2 years the costs for phasing out inefficient ACs.